Levodopa-induced dyskinesia in MPTP-treated macaques is not dependent on the extent and pattern of nigrostrial lesioning - Guigoni, Céline; Dovero, Sandra; Aubert, Incarnation; Li, Qin; Bioulac, Bernard H.; Bloch, Bertrand; Gurevich, Eugenia V.; Gross, Christian E.; Bezard, Erwan (The European journal of neuroscience, 2005)
The extent of nigrostriatal denervation is presumed to play a role in the genesis of levodopa‐induced dyskinesia. Yet some parkinsonian patients who have been treated over a long period do not develop dyskinesia, raising the possibility that the pattern of denervation is as important as the extent of lesioning as a risk factor. Here we study the extent and pattern of nigrostriatal denervation in a homogeneous population of parkinsonian macaque monkeys chronically treated with levodopa. Based on the characteristics of the lesioning, non‐dyskinetic animals could not be differentiated from those with dyskinesia. Indeed, the number of tyrosine‐hydroxylase (TH)‐immunopositive neurons in the substantia nigra pars compacta, striatal dopamine transporter (DAT) binding and TH immunostaining, as well as the overall TH striatal content measured by Western blotting were identical. Moreover, the patterns of lesioning assessed by a detailed analysis of the TH‐ and DAT‐immunopositive striatal fibers were comparable in all functional quadrants and at all rostro‐caudal levels considered. These data indicate that neither the extent nor the pattern of nigrostriatal lesioning are sufficient to explain the occurrence of levodopa‐induced dyskinesia.